Anthropology and Social Policy: Exploring Social Dynamics in Community Development - Meiyani, Eliza; Putri Sadayi, Delila; Hayan Mochammad, Fadhil (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
This research aims to analyze the impact of social policies on social dynamics and cultural change in Indonesia, with a focus on the education, health, economic empowerment, and social welfare sectors. The method used in this research is a qualitative approach, with secondary data analysis through case studies of social policies implemented between 2014 and 2024. The results show that social policies that support education and women's empowerment have a significant impact on social mobility, gender equality, and political awareness. On the other hand, the social welfare and economic empowerment sectors show a moderate impact on local cultural change. The implications of this research emphasize the importance of policies based on community participation to reduce social inequality and create more inclusive and sustainable cultural change. The findings also provide insights for improving social policies that are more responsive to social dynamics and local cultural values.